Correlation of MLCTs of Group 7 fac‐[M(CO)3]+ Complexes (M = Mn, Re) with Bipyridine, Pyridinylpyrazine, Azopyridine, and Pyridin‐2‐ylmethanimine Type Ligands for Rational photoCORM Design. Issue 33 (26th August 2019) - Kottelat, Emmanuel; Lucarini, Fiorella; Crochet, Aurelien; Ruggi, Albert; Zobi, Fabio
Abstract : A mathematical correlation of the MLCT absorption maxima of structurally related fac ‐[M(CO)3 L2 Br] complexes (M = Mn, Re; L2 = bidentate ligand) is obtained by the comparison of a total of 50 species bearing bipyridine, pyridinylpyrazine, azopyridine and pyridin‐2‐ylmethanimine L2 type ligands. The empirical relationship is first derived by the initial comparison of the MLCT absorption maxima of 26 previously published complexes and subsequently used to predict the same absorption value of 24 other species. In order to check the validity of the prediction, several new complexes were prepared. These were spectroscopically characterized and, where possible, their X‐ray solid‐state structure elucidated. The initial mathematical correlation allowed to predict MLCT absorption maxima of the unknown species with an average discrepancy of 12 nm. The relationship was subsequently refined to an average error of 6 nm with following derived formula Calc Mn m LCT = ( Obs Re MLCT /0.88) – 15.1 (where Calc Mn m LCT = predicted values of Mn complexes MLCT and Obs Re MLCT = experimentally observed MLCT transitions of Re complexes). The correlation and the formula, the significance of which are discussed, may prove useful in the long run for the rational design of Mn‐based photoCORMs starting from known data of widely investigated fac ‐[Re(CO)3 L2 Br] complexes. Abstract : Spectroscopic data of widely investigated fac ‐[Re(CO)3 L2 Br] complexes can be used to calculate MLCTs of their respective Mn congeners and thus predict wavelengths of CO photo‐release for rational Mn‐based photoCORMs design.